The use of metaphor in child psychotherapy: the development of an integrated model - Viljoen, Urshula Susanna (University of the Free State, 2003)
This theoretical study focused on the use of metaphor in psychotherapy. The aim of the study was to provide guidelines for the use of metaphor in psychotherapy and child psychotherapy. Any visible portrayal or image of psychic contents was considered to provide an externalised metaphor for these contents. Metaphors were regarded to form part of a group of representational phenomena, which function as tools portraying psychic material. The researcher adopted an integrated approach and examined the contributions of theorists representing six psychological theories. These theories were psychoanalysis, analytical psychology, Gestalt therapy, Ericksonian psychotherapy, cognitive therapy and narrative therapy. Additional individual contributions mentioned were those of Rossi, Kolb and Kalsched. Information gathered from these theories was supplemented by information from disciplines outside the field of psychology. These contributions included views on the biological processes giving rise to representational phenomena, philosophical viewpoints and viewpoints on issues of interpretation and meaning-making. An initial, tentative study was conducted, which included gaining experience with the use of metaphor in psychotherapy, specifically the sandplay method. On the grounds of this study, research questions were formulated regarding the nature of metaphor, the key concepts mentioned in relation to metaphor (focusing on the identification of general principles regarded as conducive to metaphor-use) and descriptions of the process of using metaphorical material in psychotherapy. Metaphor was found to be a complex phenomenon. This was theorised to be partly as a result of the complexity of metaphor itself and partly due to the fact that metaphor-use reflects the nature and functioning of the psyche. The psyche was approached as a functional mind-body unity. The composite nature of metaphors allows the integration of levels and dimensions of awareness, specifically the integration of experiential participation with conceptualisation and understanding. Nine key concepts were identified which could serve as general guidelines for metaphor-use. An integrated model of metaphor-use was presented, indicating the various stages of the process and the manner in which the introduction of meaning through metaphor included the activation of and the interaction with existing unconscious psychic material, leading to new or altered conceptualisations with different linking options. Since a metaphorical portrayal of psychic contents possesses its own reality, it was postulated that, bearing in mind the general guidelines provided, a therapist could apply his/her own theoretical framework to the process. However, the guidelines and the integrated model of the process of metaphor-use could make it possible for a therapist to allow his/her framework to be enriched by contributions from other approaches. Regarding the role of the therapist, the study indicated that the therapist often became responsible for that part of the process which was not carried out by the patient. It is hoped that this study could be used as a framework to structure therapy with metaphors and indicate areas for future research.

Hierdie teoretiese studie het gefokus op die gebruik van metafore in psigoterapie. Die doel van die studie was om riglyne vir die gebruik van metafore in psigoterapie en kinderpsigoterapie te ontwikkel. Enige simboliese voorstelling van psigiese inhoude is beskou as 'n metaforiese voorstelling van daardie spesifieke inhoude. Metafore word beskou as 'n groep uitbeeldingsveskynsels wat as hulpmiddels funksioneer om psigiese material weer te gee. In die navorser se benadering tot die studie is die integrasie van verskillende benaderings nagestreef. Die bydraes van ses psigologiese teorieë is bestudeer. Hierdie teorieë was psigoanalise, analitiese sielkunde, Gestalt terapie, Erickson se benadering, kognitiewe psigoterapie en narratiewe terapie. Die individuele bydraes van Rossi, Kolb en Kalsched is ook bygebring. Bykomende inligting is vanuit teorieë buite die veld van die sielkunde ingewin. Hierdie inligting het bydraes oor die onderliggende biologiese prosesse wat betrokke is by uitbeeldingsverskynsels en sekere filosofiese sienswyses ingesluit. 'n Belangrike faset van dié deel van die navorsing is die verskillende maniere waarop betekenis aan ervarings gegee word om psigiese realiteite te skep. Navorsingsvrae is geformuleer op grond van 'n aanvangstudie, wat praktiese ervaring in die gebruik van metafore in psigoterapie ingesluit het. Die 'sandplay'-metode is gebruik as voorbeeld van die gebruik van metafore in kinderpsigoterapie. Die navorsingsvrae is gebruik om die navorsing te rig. Hierdie vrae het gefokus op die aard van metafore, die identifisering van kernkonsepte rondom metafoorgebruik, en beskrywings van die proses van metafoorgebruik. Wat die kernkonsepte betref, word veral gefokus op beginsels wat bevorderlik is vir metafoorgebruik. Die studie het bevind dat die metafoor'n komplekse verskynsel is, gedeeltelik vanweë die feit dat enige uitbeelding van psigiese inhoude ook die aard en funksionering van die psige weerspieël. Die psige is benader as 'n funksionele eenheid van liggaam en denke. Aangesien die studie op die gebruik van metafore in psigoterapie gemik is, het die navorser veral gekonsentreer op twee fasette van metafoorgebruik naamlik die vermoë van 'n metafoor om eksperiensiële betrokkenheid sowel as konseptualisering en abstrakte begrip te fasiliteer. Nege sleutelkonsepte is geïdentifiseer wat riglyne vir metafoorgebruik verskaf. Daarby het die navorser 'n geïntegreerde model vir die proses van metafoorgebruik opgestel. Hierdie model maak ook voorsiening vir die rol van die terapeut. Aangesien enige metaforiese uitbeelding van psigiese inhoude 'n eie bestaansreg het, kan die voorstelling vanuit 'n betrokke terapeut se raamwerk van voorkeur benader word. Die algemene riglyne wat uit die studie geblyk het, dui egter op sekere universele aspekte van metafoorgebruik en skep die moontlikheid dat 'n terapeut sy/haar teoretiese raamwerk sou kon verryk deur insigte vanuit ander benaderings. Wat die proses van metafoorgebruik betref, is bevind dat die terapeut verantwoordelik raak vir die suksesvolle voltooiing van dié gedeelte van die proses wat die pasiënt nie self voltooi nie. Die navorser hoop dat die riglyne wat deur hierdie studie verskaf is, gebruik sal word as 'n raamwerk vir psigoterapie met metafore en tot verdere navorsing kan lei.
Thesis (Ph.D. (Psychology))--University of the Free State, 2003
Keywords: Children -- Counseling of; Metaphor -- Therapeutic use; Psychotherapy